THE POLITICAL PARTICIPATION OF CHINESE OVERSEAS IN INDONESIA AND MALAYSIA - Shasha, Huang; Darmoko, Darmoko (UI Scholars Hub, 2023)
Political participation plays an important role in protecting the interests of the Chinese overseas in Indonesia and Malaysia. This journal is qualitative research with a library approach method. This research aims to find 1) political participation patterns of Chinese Oversees in Indonesia and Malaysia; 2) factors that influence the political participation of Chinese Oversees in Indonesia and Malaysia. Chinese overseas in Indonesia and Malaysia do not actively participate in politics as the local ethnic majorities, however with the development of democracy, the Chinese overseas mainly take part in the political field by voting in national elections and regional elections, participating in political parties, joining various associations, and building close relationships with government officials. In political participation, Chinese overseas is mainly influenced by the level of democracy, political awareness, and relations with local ethics.